2006
DOI: 10.1002/art.22208
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of soluble fractalkine (CX3CL1) correlate with disease activity in rheumatoid vasculitis

Abstract: Objective. To determine levels of soluble fractalkine (sFkn) in rheumatoid arthritis (RA) patients with and without rheumatoid vasculitis (RV), and to assess the relationship of sFkn levels to disease activity.Methods. Serum was obtained from 98 RA patients (54 without vasculitis, 36 with extraarticular manifestations but without histologically proven vasculitis, and 8 with histologically proven vasculitis) and from 38 healthy individuals. Levels of sFkn were measured by enzyme-linked immunosorbent assay. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 37 publications
7
51
0
6
Order By: Relevance
“…45 In patients with autoimmune disorders, serum levels of fractalkine correlate with disease activity. [22][23][24] Given that the cellular immune response to MBP in spleen and circulating fractalkine levels were correlated in our study, it suggests that this chemokine could also be used as a marker of ongoing inflammation in the brain. Further studies to compare the histological expression of fractalkine and the cellular immune response in brain (ie, influx of lymphocytes) with circulating fractalkine levels and the Th1 response to brain are warranted.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…45 In patients with autoimmune disorders, serum levels of fractalkine correlate with disease activity. [22][23][24] Given that the cellular immune response to MBP in spleen and circulating fractalkine levels were correlated in our study, it suggests that this chemokine could also be used as a marker of ongoing inflammation in the brain. Further studies to compare the histological expression of fractalkine and the cellular immune response in brain (ie, influx of lymphocytes) with circulating fractalkine levels and the Th1 response to brain are warranted.…”
Section: Discussionmentioning
confidence: 57%
“…We also assessed serological markers of the immune response, including antibodies to MBP and systemic levels of fractalkine, because the amount of this chemokine in circulation appears to correlate with disease activity in patients with autoimmune disorders. [22][23][24] …”
mentioning
confidence: 99%
“…In inflamed local organs, such as the liver, lungs, and the kidneys, the participation of fractalkine has been recently noted [35][36][37][38][39][40] . Furthermore, increased s-fractalkine serum levels have been reported for patients with various chronic inflammatory diseases [40][41][42][43][44] . However, until now, there are no reports related to fractalkine in pancreatic inf lammator y diseases.…”
mentioning
confidence: 99%
“…The disease activity in patients with either WG or MPA is closely correlated with the markers of EC damage (Hergesell et al 1996). Moreover, we found that higher serum CX3CL1 levels are observed in patients with RV than in those with RA without vasculitis or in healthy controls (Matsunawa et al 2006). The elevated CX3CL1 levels in the RV patients are positively correlated with BVAS, VAI and serum parameters, including rheumatoid factor titers, immune complex (IC-C1q) levels, and ICAM-1 levels.…”
Section: Cx3c Chemokine 431 Cx3cl1mentioning
confidence: 64%